Open-source simulation of strongly-coupled fluid-structure interaction between non-conformal interfaces - Lewis, Nicolette S.; Winter, Andrew O.; Bonus, Justin; Motley, Michael R.; Eberhard, Marc O.; Arduino, Pedro; Lehman, Dawn E. (Frontiers in Built Environment, 2023)
Design code-based 'life-safety' requirements for structural earthquake and tsunami design offer reasonable guidelines to construct buildings that will remain standing during a tsunami or seismic event. Much less consideration has been given to assessing structural resilience during sequential earthquake and tsunami multi-hazard events. Such events present a series of extreme loading scenarios, where damage sustained during the earthquake influences structural performance during the subsequent inundation. Similar difficulties exist with respect to damage sustained during tropical events, as wind and fluid loading may vary with structural response or accumulated damage. To help ensure critical structures meet a 'life-safety' level of performance during such multi-hazard events, analysis software capable of simulating simultaneous structural and fluid dynamics must be developed. To address this gap in understanding of nonlinear fluid-structure-interaction (FSI), an open-source tool (FOAMySees) was developed for simulation of tsunami and wave impact analysis of post-earthquake nonlinear structural response of buildings. The tool is comprised of the Open-source Field Operation And Manipulation software package and OpenSeesPy, a Python 3 interpreter of OpenSees. The programs are coupled via preCICE, a coupling library for partitioned multi-physics simulation. FOAMySees has been written to work in a Linux OS environment with HPC clusters in mind. The FOAMySees program offers a partitioned conventional-serial-staggered coupling scheme, with optional implicit iteration techniques to ensure a strongly-coupled two-way FSI solution. While FOAMySees was developed specifically for tsunami-resilience analysis, it may be utilized for other FSI applications with ease. With this coupled Computational Fluid Dynamics (CFD) and Finite Element Analysis (FEA) program, tsunami and earthquake simulations may be run sequentially or simultaneously, allowing for the evaluation of nonlinear structural response to multi-hazard excitation.